2023
DOI: 10.1038/s41467-023-39684-y
|View full text |Cite
|
Sign up to set email alerts
|

Engineered MED12 mutations drive leiomyoma-like transcriptional and metabolic programs by altering the 3D genome compartmentalization

Abstract: Nearly 70% of Uterine fibroid (UF) tumors are driven by recurrent MED12 hotspot mutations. Unfortunately, no cellular models could be generated because the mutant cells have lower fitness in 2D culture conditions. To address this, we employ CRISPR to precisely engineer MED12 Gly44 mutations in UF-relevant myometrial smooth muscle cells. The engineered mutant cells recapitulate several UF-like cellular, transcriptional, and metabolic alterations, including altered Tryptophan/kynurenine metabolism. The aberrant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 86 publications
2
6
0
Order By: Relevance
“…However, the precise mechanism behind this heightened adaptability in a 3D culture context has yet to be elucidated. A recent study about MED12 Gly-44 mutations in the context of leiomyoma revealed findings in line with our results (67). While MED12 Gly-44 mutant cells displayed a proliferation deficiency under 2D culture conditions, these mutants formed notably larger spheroids in 3D spheroid environments compared to wild-type cells.…”
Section: Discussionsupporting
confidence: 93%
“…However, the precise mechanism behind this heightened adaptability in a 3D culture context has yet to be elucidated. A recent study about MED12 Gly-44 mutations in the context of leiomyoma revealed findings in line with our results (67). While MED12 Gly-44 mutant cells displayed a proliferation deficiency under 2D culture conditions, these mutants formed notably larger spheroids in 3D spheroid environments compared to wild-type cells.…”
Section: Discussionsupporting
confidence: 93%
“…The single-cell data also allows for examining how the overall tissue architecture and cellular composition change between a normal and disease state. Critically, in line with known disease pathology 1 , 38 , we noted a drastic increase in the percentage of SMC cells in UF tumors (from ~14% in myometrium to ~65% in Fibroids) (Fig. 3b ).…”
Section: Resultssupporting
confidence: 85%
“…This mutation differs from most of the previously reported MED12 mutations, which predominantly occur in exon 2 and intron 1 ( 22 , 23 ). MED12 is a constituent of the mediator complex, which acts as a key regulatory factor for the transcription of numerous genes ( 24 , 25 ). Somatic mutations in MED12 have been identified in approximately 70% of uterine leiomyomas and 10% of leiomyosarcomas ( 26 ).…”
Section: Discussionmentioning
confidence: 99%